How Habits of Culture Shape Our Rational Thinking A Comparison of Classical Greece and Ancient China. - Warden, John. (Lewiston : The Edwin Mellen Press, 2013)
A succinct yet remarkable incisive study of the complex interplay between language, modes of reading it, and modes of thinking as observed in the surviving literature of classical Greece and the roughly contemporary corpus inherited from the age of Confucius in China.
How Habits of Culture Shape Our Rational Thinking: A Comparison of Classical Greece and Ancient China; Copyright Page; Dedication; Table of Contents; Foreword; Introduction; Part One; A Deuteros Plous; Chapter 1; Chapter 2; Chapter 3; Chapter 4; B Proteron hysteron; Chapter 5; Chapter 6; Chapter 7; Part Two; Chapter 8; Chapter 9; Chapter 10; Chapter 11; Epilegomena; Glossary; Selected Bibliography; Index
Description based upon print version of record.
Keywords: Classical literature -- History and criticism; Philosophy, Ancient; Philosophy, Chinese; Philosophy, Ancient; Philosophy, Chinese; PHILOSOPHY / Eastern; LITERARY CRITICISM / Ancient & Classical; Electronic books